Increased plasminogen activator inhibitor results in a hypofibrinolytic state in adolescents with obesity: in vivo and ex vivo evidence. (19th July 2016) - Dietrich, Kevin; Ball, Geoff D. C.; Mitchell, Lesley G.
Summary: Obesity in adolescents increases their risk for deep vein thrombosis. The objectives of this study were to determine potential mechanisms for thrombotic risk by investigating the fibrinolytic pathway in a sample of adolescents with and without obesity. Thirty‐seven adolescents with obesity and 16 normal weight age‐matched controls were recruited. Plasma levels of components of the fibrinolytic system were measured in addition to a Global Haemostasis Potential assay (GHP), which assesses plasma capacity to generate and lyse a fibrin clot. Levels of plasminogen activator inhibitor (PAI) and tissue plasminogen activator (tPA)/PAI complexes were increased in adolescents with obesity when compared to normal weight controls. There was a significant inverse association of increasing PAI with a decrease in plasmin‐antiplasmin complexes. The GHP in obese adolescents displayed a hypofibrinolytic response with a markedly increased t½ clot lysis time, as well as an increase in fibrin clot density as indicated by increased absorbance at maximum peak height. In the obese group, immunodepletion of PAI decreased both t½ lysis time and absorbance at maximum peak height. We have shown in vivo and ex vivo there is a hypofibrinolytic state in obese adolescents and have established the hypofibrinolytic state is due to increased PAI levels.